Plant Cell and Tissue Culture
DOI: 10.1385/0-89603-161-6:227
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Micropropagated Plantlets for Transfer to Soil Without Acclimatization

Abstract: Plantlets cultured in vitro on agar-based media in a water-saturated atmosphere wilt rapidly when transferred to normal greenhouse or field conditions. Water is rapidly lost from the leaves because stomata fail to respond to those stimuli that normally induce closure (1-4), and poor development of epicuticular wax results in loss of water through the cuticle (5-7). Uptake of water by the roots is limited by damage incurred during transplantation and by poor contact with the substrate. Problems of transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Before transplanting to the greenhouse, the normalized plants from all cultivars were transplanted to small pots containing peat-based soil and were acclimatized in the growth chamber for about one week, as hardening the plantlets at the transitions from in vitro to ex vitro is necessary to increase the survival of transplants [ 29 ]. In our study, all plantlets were observed to survive during the acclimatization period and maintained their survival rate when transferred to the greenhouse ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Before transplanting to the greenhouse, the normalized plants from all cultivars were transplanted to small pots containing peat-based soil and were acclimatized in the growth chamber for about one week, as hardening the plantlets at the transitions from in vitro to ex vitro is necessary to increase the survival of transplants [ 29 ]. In our study, all plantlets were observed to survive during the acclimatization period and maintained their survival rate when transferred to the greenhouse ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Roberts et al (1990) found that placing the culture vessels on a cooled shelf could harden the plantlets. In the current study, we investigated the growth patterns of regenerants that were kept in growth chambers under a 16-h photoperiod at either 4~ or 24~ Many of the regenerants grew successfully at 4~ but died when held at 24~ This demonstrates the positive effect of a cold treatment before transplantation of H. orientalis plantlets.…”
Section: Discussionmentioning
confidence: 99%
“…When transferred to the field, plants grown in vitro were unable to interact with soil microbes or adjust to their surroundings [46]. It is vital to guarantee that the plants are planted in a moist environment for 2-4 weeks, depending on the rate of new leaf and root creation, in order to prolong life after transplantation to in vivo settings [47,48].…”
Section: Gladiolus In Vitro Propagation: Advantages and Applicationsmentioning
confidence: 99%
“…In vitro-grown plantlets were unable to engage with soil microbes and were also unable to cope with environmental conditions after field transfer [46]. In order to maximize survival after transplantation of plants to in vivo conditions, it is necessary to ensure that plantlets grow in a humid environment over a period of 2-4 weeks, depending on the rates at which new leaves and roots are produced [47,48]. According to one study, Cantor and Tolety [154] gladiolus could withstand temperatures as low as 5 • C and as high as 32 • C. As a result, acclimating outside is not advised.…”
Section: Ex Vitro Acclimatizationmentioning
confidence: 99%